Contribution Analysis (Better Evaluation)
Contribution Analysis is an approach for assessing causal questions an d inferring causality in real-life program evaluations. It offers a st ep-by-step approach designed to help managers, researchers, and policy makers arrive at conclusions about the contribution their program has made (or is currently making) to particular outcomes. The essential va lue of contribution analysis is that it offers an approach designed to reduce uncertainty about the contribution the intervention is making to the observed results through an increased understanding of why the observed results have occurred (or not!) and the roles played by the i ntervention and other internal and external factors. Contribution anal ysis is particularly useful in situations where the programme is not e xperimental, i.e. not in trial projects but in situations where the pr ogramme has been funded on the basis of a relatively clearly articulat ed theory of change and where there is little or no scope for varying how the program is implemented. Contribution analysis helps to confirm or revise a theory of change; it is not intended to be used to surfac e or uncover and display a hitherto implicit or inexplicit theory of c hange. The report from a contribution analysis is not definitive proof , but rather provides evidence and a line of reasoning from which we c an draw a plausible conclusion that, within some level of confidence, the program has made an important contribution to the documented resul ts.